A Study of the Factors Impeding Proper Dietary Habits: An Investigation Using the Japanese Comprehensive Survey of Living Conditions - Akira Komatsuzaki; Sachie Ono; Kanako Mitomi; Kiyoka Arashi; Yukika Enoki; Kanako Seino; Naru Komatsuzaki; Yuuko Ikeda (Clinics and Practice, 2024)
(1) Background: Diet is significant for nutritional intake and serves as an essential element for improving quality of life (QOL). Poor dietary management skills increase the risk of onset or progression of lifestyle-related diseases, and, in particular, are a factor in reduced QOL during old age. This study aimed to clarify the physical and social background factors impeding dietary self-management. (2) Methods: The study participants were 3814 men (age range, 30–69 years) extracted from anonymous data comprising 15,294 persons provided from the Japanese national statistics database. The participants were classified into two groups (Concerned vs. Unconcerned) according to whether they were concerned about their diet. Adjusted odds ratios (ORs) for diet-conscious behaviors were then obtained by means of binomial logistic regression analysis performed following univariate analysis. (3) Results: The Concerned and Unconcerned groups comprised 2548 (66.8%) and 1266 subjects (33.2%), respectively. The diet-conscious behavior with the highest response rate was eating regularly (46.7%). The most frequent items in the Unconcerned group were the subjective symptom “irritable” (48.9%), high stress (46.3%), working more than 56 h/week (43.8%), and smoking (41.9%). The only item with a large significant OR in the binomial logistic regression analysis was smoking (OR: 2.2). (4) Conclusions: These results suggest that a smoking habit and stress are factors that impede diet management behaviors.